Investigating the Role of Cooperative Learning in Fostering Moroccan ESP Students’ Learning Attitudes - Hanae Ait Hattani (Journal of English Language Teaching and Linguistics, 2024)
Cooperative learning (CL) is a teaching and learning approach that has been sufficiently studied to be accepted as an effective method of language education, English language in particular. In all levels of education, students in cooperative situations achieved greater academic, social, and psychological benefits. Nowadays, learners are expected to be more actively involved in the teaching and learning process, especially when they work together to achieve a specific target or objective. This study investigates teaching English for Specific Purposes within the paradigm of a cooperative learning approach. It comes as an attempt to investigate the impact of cooperative learning on improving students’ learning skills and attitudes in the ESP instructional context. Through a survey questionnaire, this inquiry aimed at shedding light on learners’ perceptions towards’ their cooperative learning experience. Based on attitudinal results, the majority of respondents positively perceived the use of cooperative learning as an approach that provides them with a learning environment conducive to social interaction, peer tutoring, skills’ development, and knowledge retention. Eventually, according to the study results, cooperative learning has benefits that go outside of the classroom and learning environment. Long-term benefits of cooperative learning include the opportunity for students to practice skills that may have a progressive impact on their lives in addition to helping them acquire new knowledge.